(untitled) (Fiep Bulletin - online, 2011)
Currently, the nature of human work provides a means of comfort and ease to perform the tasks, favoring a sedentary lifestyle, bad posture and repetitive movements. Computer use encourages the development of Repetitive Strain Injury / Work-Related Musculoskeletal Disorders of the characteristics of work. Among lawyers, it appears that everyone must make use of computer, remaining in a seated position much of the work day, exposing them to risk of developing Work-Related Musculoskeletal Disorders. This study is focused on quantity and descriptive in nature. It was held in the lobby of the Civil Court of Curitiba Forum during the event of a Week of Health of the Bar Association of Brazil (OAB) - section of Parana. Was conducted with 29 lawyers who agreed to answer a questionnaire and receive guidance on the risks and means of prevention of Work-Related Musculoskeletal Disorders. Consisted of a structured questionnaire including open and closed. After answering the questionnaire the subjects were guided through folder on posture, proper positioning before the computer and loading of cargo, in this case processes. The results were that 52% of lawyers are sedentary, while 45% work using laptops, 17% feel somewhat tired at the end of the workday and 34% very tired mentally, 79% work in sitting posture and 79% work more than 8 hours per day. We conclude that it is extremely important for collective action orientation of the population regarding the prevention of Repetitive Strain Injuries and Work-Related Musculoskeletal Disorders.